Long-term smoking cessation rates in elderly versus other adult smokers: A 3-year follow-up study in Taiwan. (December 2018) - Hsu, Chiao-Lin; Hsueh, Kuang-Chieh; Chou, Ming-Yueh; Yu, Hsien-Chung; Mar, Guang-Yuan; Chen, Hong-Jhe; West, Robert
Abstract: Introduction: Smoking cessation improves life expectancy at any age. There is some evidence that elderly smokers have at least as good a chance of successfully stopping as other smokers but direct comparisons with long-term follow up are rare. This study aimed to compare success rates up to 3 years in smokers aged 65+ versus other adult smokers with and without adjustment for a range of other smoker characteristics. Methods: This was a prospective study of 1065 smokers who attended a stop-smoking clinic in Taiwan. Participants (896 < 65 years, 169 65+ years) were followed up by telephone 3, 6, 12 and 36 months after the initial quit date. Prolonged abstinence (abstinent at all follow-ups) and point prevalence abstinence (7 days prior to final follow up) were compared between 'elderly' participants aged 65+ years versus 'non-elderly' participants aged <65 years with and without adjustment for a range of baseline smoker characteristics (sex, educational level, previous quit attempts, cigarette dependence score). Non-responders were considered to be smoking. Results: Prolonged 36-month abstinence rates were 20.1% (N = 34) and 15.3% (N = 137) in the elderly and non-elderly participants respectively (p = 0.137). Point prevalence 36-month abstinence rates were 37.3% (N = 63) and 26.5% (N = 237) in the elderly and non-elderly participants respectively (p = 0.005). The odds ratios comparing elderly versus non-elderly abstinence rates after adjustment for baseline variables were 1.17 (95%CI = 0.75–1.83) and 1.52 (95%CI = 1.05–2.20) for prolonged abstinence and point prevalence abstinence respectively. Conclusions: Elderly smokers attending smoker clinics in Taiwan appear to be at least as likely to achieve long-term abstinence as other adult smokers. Highlights: Prolonged 36-month abstinence rates were higher in the elderly group. Point prevalence 36-month abstinence rates were also higher in the elderly group. and non-elderly participants respectively.